Assessment of the Physiological Response and Productive Performance of Vegetable vs. Conventional Soybean Cultivars for Edamame Production - Ribera, Laura Matos [UNESP]; Aires, Eduardo Santana [UNESP]; Neves, Caio Scardini [UNESP]; Fernandes, Gustavo Do Carmo [UNESP]; Bonfim, Filipe Pereira Giardini [UNESP]; Rockenbach, Roanita Iara; Rodrigues, João Domingos [UNESP]; Ono, Elizabeth Orika [UNESP] (MDPI, 2022)
Because there is a close relationship between plant physiological response and crop performance, the current study aims to evaluate the photosynthetic efficiency and productive performance of vegetable versus conventional soybean cultivars for edamame production. The study was conducted at the School of Agriculture (FCA UNESP), Botucatu-SP, Brazil. The treatments in this study included soybean cultivars: vegetable-type BRS 267, vegetable-type BRSMG 790A), and type soybean cultivar grain 58HO124 EP RR, with ten repetitions per treatment in a completely randomized block design. Gas exchange and the response of the cultivars to light were evaluated for photosynthetic characterization. The first pod insertion height, plant height, number of pods per plant, and production in immature grains were all assessed for cultivar productive performance. The type of soybean cultivar grain and vegetable types of soybean showed different behaviors on physiology and yield. The vegetable-types BRS 267 and BRSMG 790A had the highest average for first pod insertion height. The vegetable type BRS 267, whose photoassimilates were designated for vegetative development, had the greatest average plant height. The conventional type 58HO124 EP RR showed greater assimilation of CO2; however, the photoassimilates were directed to floral emission because such features are inherent in its ability. Finally, vegetable-type BRSMG 790A produced the most immature grains per plant while also having the greatest first pod insertion height, being the best in converting photoassimilates for edamame production.
Keywords: edamame; photosynthesis; production potential; soybean type